Multiband Metamaterial Absorber in a Ring Structure Base on High-order Magnetic Resonance - Nguyen, Thi Hien; Nguyen, Thi Anh Hong; Dinh, Thi Nga; Bui, Xuan Khuyen; Bui, Son Tung; Nguyen, Xuan Ca; Nguyen, Van Ngoc; Nguyen, Ba Tuong; Vu, Dinh Lam (Communications in Physics, 2021)
We proposed a multi-band metamaterial absorber (MA) based on high-order magnetic resonance using ring-shaped structures. We obtained three absorption peaks at 4.71 GHz (the fundamental resonance), 13.39 GHz (the third-order behavior), and 19.91 GHz (the fifth-order behavior) with correspondent absorptions of 90%, 100%, and 99.33%, respectively. Therefore, these high-order perfect absorptions are the potential to make the easier fabrication for the next generation of MAs, especially in high-frequency regions. Particular, the obtained results are further controlled using the LC circuit model. Besides, by scaling down the unit-cell size, the third- and fifth-order absorptions are created in the THz frequency band